2016
DOI: 10.1038/ngeo2795
|View full text |Cite
|
Sign up to set email alerts
|

Methane emissions proportional to permafrost carbon thawed in Arctic lakes since the 1950s

Abstract: Permafrost thaw exposes previously frozen soil organic matter to microbial decomposition. This process generates methane and carbon dioxide, and thereby fuels a positive feedback process that leads to further warming and thaw1. Despite widespread permafrost degradation during the past ~40 years2, 3, 4, the degree to which permafrost thaw may be contributing to a feedback between warming and thaw in recent decades is not well understood. Radiocarbon evidence of modern emissions of ancient permafrost carbon is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
128
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 164 publications
(140 citation statements)
references
References 50 publications
9
128
0
Order By: Relevance
“…Multiple studies have found that edges of actively thawing wetlands are hotspots for microbial processing of organic matter, including methane production, and assumed responses were driven by inputs of recently thawed permafrost carbon, which is easily degraded by microbes and often co-occurs with other nutrients (Abbott et al, 2014;Anthony et al, 2016;Finger et al, 2016;Keuper et al, 2012;Klapstein et al, 2014;Neumann et al, 2016;Turetsky et al, 2002). Our data suggest another plausible mechanism.…”
Section: Post-rain Recharge Creates Spatial Gradients In Bog Soil Temmentioning
confidence: 58%
“…Multiple studies have found that edges of actively thawing wetlands are hotspots for microbial processing of organic matter, including methane production, and assumed responses were driven by inputs of recently thawed permafrost carbon, which is easily degraded by microbes and often co-occurs with other nutrients (Abbott et al, 2014;Anthony et al, 2016;Finger et al, 2016;Keuper et al, 2012;Klapstein et al, 2014;Neumann et al, 2016;Turetsky et al, 2002). Our data suggest another plausible mechanism.…”
Section: Post-rain Recharge Creates Spatial Gradients In Bog Soil Temmentioning
confidence: 58%
“…For example, lake shore erosion rapidly degrades permafrost around lakes and releases organic C to the aquatic environment. Shore erosion not only affects the active layer soils from the top but does affect deeper permafrost soil layers (Walter Anthony et al, 2016). This vulnerability of large currently frozen C pools to thaw highlights the importance of deep permafrost organic C to be considered in future C cycle models.…”
Section: The Fate Of Organic Carbon In Thermokarst-affected Yedoma Inmentioning
confidence: 99%
“…Due to its syngenetic formation history, Yedoma deposits store large amounts of organic carbon which are vulnerable to mobilization upon thaw [5,6]. Therefore, Yedoma degradation contributes to climate warming through the release of greenhouse gases from microbial decomposition of thawed organic carbon [7,8].…”
Section: Introductionmentioning
confidence: 99%